Analyzing Grammar Usage in Indonesian Travel Website - Wardhana, I Gede Neil Prajamukti; Dewi, Ni Luh Desy Suari (International Journal of Linguistics and Discourse Analytics, 2025)
Tourism website plays the important role to shape cultural perceptions and promoting destinations, to make language use a significant factor in influencing potential visitors. Despite extensive theoretical discussions on grammar's role in discourse. It remains a gap between linguistic theories and their practical application in the tourism industry, particularly in how grammar contributes to cultural representation. This gap matters because in tourism promotion, nuanced grammatical choices can change influence visitors' emotional connection, trust, and desire to experience a culture, ultimately affecting destination appeal and competitiveness. This study aims to bridge this gap by analyzing the grammatical strategies used by Indonesian travel websites to construct narratives about Bali's cultural identity. To combine the Systemic Functional Linguistics (SFL) and cultural semiotics as the analytical framework, the research focused on the ideational, interpersonal, and textual metafunctions of language to uncover how deeper cultural meanings are encoded. The data collected from popular Indonesian travel websites, targeting content on cultural landmarks, traditional performances, and local customs in Bali. Textual excerpts were manually extracted and systematically organized for analysis. The findings showed that the websites mainly use descriptive language, personal pronouns, commands, and connecting words to portray Bali as a genuine, spiritual, and unique place to visit. Additionally, culturally specific terms and sensory descriptions enrich the promotional narratives, enhancing reader engagement and positioning Bali as a culturally immersive experience. The research concluded that grammatical choices were instrumental not only in communication but also to shape cultural tourism narratives. By doing these strategies, the study contributes to both linguistic and tourism discourse, offering practical insights into the effective use of grammar for cultural representation and promotional purposes.